Evidence of Neutralizing and Non-Neutralizing Anti-Glucosaminidase Antibodies in Patients With S. Aureus Osteomyelitis and Their Association With Clinical Outcome Following Surgery in a Clinical Pilot - Sherchand, Shardulendra Prasad; Adhikari, Rajan P.; Muthukrishnan, Gowrishankar; Kanipakala, Tulasikumari; Owen, John R.; Xie, Chao; Aman, M. Javad; Proctor, Richard A.; Schwarz, Edward M.; Kates, Stephen L. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus osteomyelitis remains a very challenging condition; recent clinical studies have shown infection control rates following surgery/antibiotics to be 60%. Additionally, prior efforts to produce an effective S. aureus vaccine have failed, in part due to lack of knowledge of protective immunity. Previously, we demonstrated that anti-glucosaminidase (Gmd) antibodies are protective in animal models but found that only 6.7% of culture-confirmed S. aureus osteomyelitis patients in the AO Clinical Priority Program (AO-CPP) Registry had basal serum levels (>10 ng/ml) of anti-Gmd at the time of surgery (baseline). We identified a small subset of patients with high levels of anti-Gmd antibodies and adverse outcomes following surgery, not explained by Ig class switching to non-functional isotypes. Here, we aimed to test the hypothesis that clinical cure following surgery is associated with anti-Gmd neutralizing antibodies in serum. Therefore, we first optimized an in vitro assay that quantifies recombinant Gmd lysis of the M. luteus cell wall and used it to demonstrate the 50% neutralizing concentration (NC50) of a humanized anti-Gmd mAb (TPH-101) to be 15.6 μg/ml. We also demonstrated that human serum deficient in anti-Gmd antibodies can be complemented by TPH-101 to achieve the same dose-dependent Gmd neutralizing activity as purified TPH-101. Finally, we assessed the anti-Gmd physical titer and neutralizing activity in sera from 11 patients in the AO-CPP Registry, who were characterized into four groups post-hoc. Group 1 patients (n=3) had high anti-Gmd physical and neutralizing titers at baseline that decreased with clinical cure of the infection over time. Group 2 patients (n=3) had undetectable anti-Gmd antibodies throughout the study and adverse outcomes. Group 3 (n=3) had high titers +/− neutralizing anti-Gmd at baseline with adverse outcomes. Group 4 (n=2) had low titers of non-neutralizing anti-Gmd at baseline with delayed high titers and adverse outcomes. Collectively, these findings demonstrate that both neutralizing and non-neutralizing anti-Gmd antibodies exist in S. aureus osteomyelitis patients and that screening for these antibodies could have a value for identifying patients in need of passive immunization prior to surgery. Future prospective studies to test the prognostic value of anti-Gmd antibodies to assess the potential of passive immunization with TPH-101 are warranted.